Drivers of telemedicine use: International evidence from three samples of physicians - Francesc Saigí-Rubió; Joan Torrent Sellens; Ana Isabel Jiménez-Zarco (Internet Interdisciplinary Institute, Open University of Catalonia, 2014)
The aim of the working paper is to analyse the determinants of telemedicine use. To that end, the study makes two basic contributions. First, it considers six working hypotheses in the context of technology acceptance models (TAMs). Second, it uses data obtained for three samples of 510 physicians: 113 in Spain, 118 in Colombia and 279 in Bolivia, and it performes binary logistic regression. In the three samples, it was found that the physician's level of ICT use in his/her personal life was the variable that had the highest explanatory power on telemedicine use. In the Spanish sample, the physicians' perceived ease-of-use of ICTs in clinical practice and propensity to innovate were the two other variables that determined telemedicine use, whereas in the Colombian and Bolivian samples, it was the level of optimism about ICTs. The results showed a more complete model that contemplated personal, usability and innovatory aspects in the explanation of telemedicine use in Spain, whereas the results for the Latin American samples indicated a more primary model in the explanation of telemedicine use, which was completed by an optimism factor that did not emerge in the Spanish sample.
Keywords: I12; I14; I31; 330; Telemedicine; eHealth; Technology Acceptance Models (TAM)